Neuroprotective influence of taurine on fluoride-induced biochemical and behavioral deficits in rats (2017)
Epidemiological and experimental studies have demonstrated that excessive exposure to fluoride induced neurodevelopmental toxicity both in humans and animals. Taurine is a free intracellular b- amino acid with antioxidant and neuroprotective properties. The present study investigated the neu- roprotective mechanism of taurine by evaluating the biochemical and behavioral characteristics in rats exposed to sodium fluoride (NaF) singly in drinking water at 15 mg/L alone or orally co-administered by gavage with taurine at 100 and 200 mg/kg body weight for 45 consecutive days. Locomotor behavior was assessed using video-tracking software during a 10-min trial in a novel environment while the brain structures namely the hypothalamus, cerebrum and cerebellum of the rats were processed for biochemical determinations. Results showed that taurine administration prevented NaF-induced loco- motor and motor deficits namely decrease in total distance travelled, total body rotation, maximum speed, absolute turn angle along with weak forelimb grip, increased incidence of fecal pellets and time of grooming, immobility and negative geotaxis. The taurine mediated enhancement of the exploratory profiles of NaF-exposed rats was supported by track and occupancy plot analyses. Moreover, taurine prevented NaF-induced increase in hydrogen peroxide and lipid peroxidation levels but increased acetylcholinesterase and the antioxidant enzymes activities in the hypothalamus, cerebrum and cere- bellum of the rats. Collectively, taurine protected against NaF-induced neurotoxicity via mechanisms involving the restoration of acetylcholinesterase activity and antioxidant status with concomitant inhi- bition of lipid peroxidation in the brain of rats.